Redescriptions of ten endemic Cytherissa species (Ostracoda, Podocopida, Cytherideidae) from the coastal and deep-water zones of Lake Baikal - Alekseeva, Tatyana M.; Krivorotkin, Roman S.; Timoshkin, Oleg A. (Zootaxa, 2025)
Lake Baikal is a unique biodiversity hotspot of ostracods, especially of the representatives of the genus Cytherissa Sars, 1925. By now, over 57 endemic species and subspecies of the genus have been reported in this area, and this number can become, at least, twice as that. Most of available descriptions of endemic Baikalian ostracods (especially Cytherissa) are, regrettably, brief and the morphology of all species requires detailed examination by scanning electron microscopy. Based on a type collection of specimens of a well-known researcher of Baikalian ostracods, G.F. Mazepova, we provide illustrated morphological redescriptions of 10 poorly studied endemic Baikalian species: Cytherissa glomerata Mazepova, 1990, Cytherissa dubitabilis (Bronstein, 1947) Mazepova 1990, Cytherissa derupta Mazepova, 1984, Cytherissa cytheriformis Bronstein, 1947, Cytherissa golyschkinae Mazepova, 1990, Cytherissa obrutshevi Mazepova, 1990, Cytherissa calva Mazepova, 1990, Cytherissa plena Mazepova, 1985, Cytherissa bisetosa Mazepova, 1984 and Cytherissa sinistra Mazepova, 1984. We carefully examined the carapace morphology of these species using scanning electron microscopy, analyzed the structure of limbs and hemipenes, and briefly characterized their ecology. This work includes detailed discussions of the nomenclatural acts referring to the type specimens of each of the ten species. The majority of them include selected lectotypes and paralectotypes, and some—neotypes.